The Association of Pseudohypoparathyroidism Type Ia with Chiari Malformation Type I: A Coincidence or a Common Link? - Paria Kashani; Madan Roy; Linda Gillis; Olufemi Ajani; M. Constantine Samaan (Case Reports in Medicine)
A 19-month-old boy was referred for progressive weight gain. His past medical history included congenital hypothyroidism and developmental delay. Physical examination revealed characteristics of Albright Hereditary Osteodystrophy, macrocephaly, and calcinosis cutis. He had hypocalcemia, hyperphosphatemia, and elevated Parathyroid Hormone levels. Genetic testing revealed a known mutation of GNAS gene, confirming the diagnosis of Pseudohypoparathyroidism Type Ia (PHP-Ia) (c.34C>T (p.G1n12X)). He had a normal brain MRI at three months, but developmental delay prompted a repeat MRI that revealed Chiari Malformation Type I (CM-I) with hydrocephalus requiring neurosurgical intervention. This was followed by improvement in attaining developmental milestones. Recently, he was diagnosed with growth hormone deficiency. This case suggests the potential association of CM-I with PHP-Ia. Larger studies are needed to assess whether CM-I with hydrocephalus are common associations with PHP-Ia and to define potential genetic links between these conditions. We propose a low threshold in performing brain MRI on PHP-1a patients, especially those with persistent developmental delay to rule out CM-I. Early intervention may improve neurodevelopmental outcomes and prevent neurosurgical emergencies.